Implementation of guideline-recommended organ-protective therapy in people with type 2 diabetes and cardiovascular disease, heart failure, or kidney disease: real-world evidence from a German University Hospital - Suliman, Karzan; Lee-Barkey, Young Hee; Brehmer, Alexander; Stratmann, Bernd; Klose, Jasmin M.; Lenfers, Tim; Kleesiek, Jens; Reger-Tan, Susanne; Keyl, Julius (Frontiers in Endocrinology, 2026)
BackgroundOrgan-protective therapy with sodium-glucose cotransporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP1RA) is recommended for people with type 2 diabetes (PwT2D) and cardiorenal comorbidities, yet real-world uptake remains uncertain.MethodsUsing the University Hospital Essen FHIR data lake (2019–2024), we identified PwT2D and cardiorenal comorbidities qualifying for organ-protective therapy [atherosclerotic cardiovascular disease (ASCVD/high ASCVD risk), heart failure (HF), chronic kidney disease (CKD)] by International Classification of Diseases (ICD-10) diagnoses, German surgery procedure codes (OPS), and clinical data. Guideline adherence and treatment trends were assessed by Anatomical Therapeutic Chemical (ATC) medication data for SGLT2i and GLP1RA. Group differences and factors associated with guideline adherent therapy were analyzed using X²-test and multivariable modeling.ResultsThe total cohort comprised 19,684 individuals (age: 70.3 ± 11.2 years, female sex: 36.8%, mean HbA1c 7.2 ± 1.5%, BMI 29.7 ± 6.4 kg/m²). In group analysis, female sex was the most prominent difference with lower rates of women among those treated with SGLT2i and/or GLP1RA with small to moderate effect size (standardized mean difference 0.48). Guideline adherent therapy with SGLT2i and/GLP1RA increased steadily from 10.2% to 48.7% in PwT2D eligible for organ-protective therapy. Treatment rates varied by comorbidity and drug class, with the lowest overall uptake observed in people with T2D and CKD (32.5%) and the highest in those with all three cardiorenal comorbidities (63.9%). Among drug classes, SGLT2i use was 44.7%, GLP1RA use was 9.5%, and combination therapy remained low at 5.5%. Female sex (OR 0.76, 95% CI 0.66-0.89, p<0.001), and higher age (OR 0.98, 95% CI 0.99-0.97, p<0.0001) reduced the likelihood, while higher number of comorbidities (OR 1.26, 95% CI 1.18-1.34, p<0.0001) and higher number of medication (OR 1.98, 95% CI 1.88-2.08, p<0.0001) increased the likelihood of guideline adherent therapy.ConclusionsGuideline recommendations for organ protection in PwT2D and cardiorenal comorbidities are increasingly reflected in clinical practice, yet a substantial care gap persists, with the majority of individuals remaining untreated. Certain subpopulations - particularly women - are underrepresented among those receiving guideline adherent therapy. Further research into the causes of undertreatment and development of targeted implementation strategies is needed to close remaining evidence–practice gaps.